2022
DOI: 10.1002/phar.2679
|View full text |Cite
|
Sign up to set email alerts
|

Use of oral anticoagulants among individuals with cancer and atrial fibrillation in the United States, 2010–2016

Abstract: Background Anticoagulation among patients with cancer and atrial fibrillation is challenging due to elevated risk of bleeding and stroke. We characterized use of oral anticoagulants among patients with cancer and non‐valvular atrial fibrillation (NVAF). Methods We used Surveillance, Epidemiology, and End Results (SEER)‐Medicare data and included patients with cancer aged ≥66 years with an incident diagnosis of NVAF from 2010 to 2016. We used a Cox proportional hazard model and multivariable logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
(94 reference statements)
2
3
0
Order By: Relevance
“…Moreover, our findings also highlighted that when patients are stratified by socioeconomic deprivation, the difference in OAC prescribing between patients with and without cancer remained relatively constant across all quintiles, with the most deprived quintile having the lowest probability of OAC prescribing overall regardless of cancer status. These findings are consistent with previous data from the United States that looked at OAC prescribing in patients with cancer with AF 35 . These results also reflect on what we have observed earlier in our previous analysis, that socioeconomic inequalities in the prescribing of OACs in England exist, with low socioeconomic status associated with the prescription of aspirin only or no treatment compared with patients with higher socioeconomic status 15 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, our findings also highlighted that when patients are stratified by socioeconomic deprivation, the difference in OAC prescribing between patients with and without cancer remained relatively constant across all quintiles, with the most deprived quintile having the lowest probability of OAC prescribing overall regardless of cancer status. These findings are consistent with previous data from the United States that looked at OAC prescribing in patients with cancer with AF 35 . These results also reflect on what we have observed earlier in our previous analysis, that socioeconomic inequalities in the prescribing of OACs in England exist, with low socioeconomic status associated with the prescription of aspirin only or no treatment compared with patients with higher socioeconomic status 15 .…”
Section: Discussionsupporting
confidence: 92%
“…States that looked at OAC prescribing in patients with cancer with AF. 35 These results also reflect on what we have observed earlier in our previous analysis, that socioeconomic inequalities in the prescribing of OACs in England exist, with low socioeconomic status associated with the prescription of aspirin only or no treatment compared with patients with higher socioeconomic status. 15 In our previous work, we also captured ethnic inequalities in the care of patients with AF 15 ; however, in this study, we could not exclude the possibility of ethnic inequalities in OAC prescribing between patients with and without cancer because of the small number of ethnic groups per cancer type.…”
Section: Discussionsupporting
confidence: 89%
“…From 2011 to 2016, the use of DOACs increased from 21.8% to 76.2% and the use of warfarin decreased from 78.2% to 23.8%. At this time, DOACs are recommended instead of warfarin therapy for patients with atrial fibrillation, but there are no specific and widely accepted guidelines for the anticoagulation of patients with protein S deficiency, especially in the setting of TAVR [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective database analysis from Taiwan reported that the use of dabigatran might be linked to a reduced risk of mortality from all causes and cancer-related causes when compared to rivaroxaban [ 133 ]. However, in recent decades, an increase in DOACS use in cancer patients has been observed, although a considerable proportion of them remain without anticoagulation [ 134 ]. Moreover, the use of DOACs in this subset of patients has been recently encouraged [ 118 ].…”
Section: Doacs In Patients With Atrial Fibrillation and Malignancymentioning
confidence: 99%